A multicenter, randomized, double-blind, controlled study to evaluate the efficacy and safety of dantrolene on ventricular arrhythmia as well as mortality and morbidity in patients with chronic heart failure (SHO-IN trial): rationale and design. Issue 4 (April 2020) - Kobayashi, Shigeki; Wakeyama, Takatoshi; Ono, Shiro; Ikeda, Yasuhiro; Omura, Masato; Oda, Tsuyoshi; Hisamatsu, Yuji; Seki, Kozaburo; Satoh, Akira; Hiromoto, Mitsuyuki; Akashi, Shintaro; Uchida, Kosuke; et al.
Highlights: Ca 2+ leakage through the ryanodine receptor (RyR2) is one of the causes of heart failure. RyR2-targeting therapy by dantrolene suppresses the Ca 2+ leakage through RyR2. The trial will clarify the efficacy of dantrolene for heart failure and arrhythmia. Abstract: Background: Leakage of Ca 2+ from the sarcoplasmic reticulum (SR) is a critical contributing factor to heart failure pathophysiology. Therefore, reducing SR Ca 2+ leaks may provide significant additive benefits when used in combination with conventional therapies. Dantrolene, a drug routinely used to treat malignant hyperthermia, also stabilizes the cardiac isoform of the release channel (RyR2), thus decreasing SR Ca 2+ leaks. The purpose of this study is to evaluate the effect of chronic administration of dantrolene on heart failure and lethal arrhythmia in patients with chronic heart failure and reduced ejection fraction in a multicenter, randomized, double-blind, controlled study. Methods: Patients with chronic heart failure who had functional status of New York Heart Association class II and III and a left ventricular ejection fraction <40% were treated according to the Japanese Circulation Society, the European Society of Cardiology, and the American Heart Association/the American College of Cardiology guidelines for diagnosis and treatment of acute and chronic heart failure. Patients were randomized and divided into two groups in a double-blind fashion: dantrolene group and placebo group (target sample size: 300 cases). These drugs were administered for 96 weeks. The primary endpoint is cardiovascular death, first hospitalization for exacerbation of heart failure, or lethal arrhythmia [ventricular tachycardia (VT) storm, sustained VT, ventricular fibrillation] for 2 years after starting administration of dantrolene 1 cap (25 mg) three times daily (if not tolerable, two times daily) or matching placebo. Results: This paper presents the rationale and trial design of the study. Recruitment for the study started on 8 December 2017. Conclusions: The results of this trial will clarify the efficacy and safety of dantrolene for ventricular arrhythmia, as well as mortality and morbidity in patients with chronic heart failure and reduced ejection fraction during guideline-directed medical treatment.